Musculoskeletal immune‐related adverse events with the use of checkpoint inhibitors in malignancy. Issue 5 (10th May 2022) - Dey, Abhishikta; Manolios, Nicholas; Long, Georgina V.; Carlino, Matteo S.; Kefford, Richard; Schrieber, Leslie
Abstract: Background: Immunotherapy has revolutionised the treatment of many malignancies. Along with their success, there have been inflammatory and immune‐related adverse events (irAE). There is a paucity of literature describing the Australian experience of rheumatic irAE. Aims: To describe and characterise the Royal North Shore Hospital and Westmead Hospital cohort with rheumatic irAE. Methods: This case series reports on 17 patients with advanced cancer treated at two sites in Sydney, Australia who were referred for rheumatological evaluation from 2013 to 2016. Data were collected retrospectively and inspected for clinical signs, duration of immunotherapy prior to onset of symptoms, management strategies and cancer outcomes. Results: Patients presented with arthralgias, myalgias, periarticular and systemic symptoms. Onset of rheumatological symptoms was variable, with a median of 4 months (range 0.2–24) for monotherapy and 5.05 months (range 0.2–6.9) for combination. The predominant findings were of tenosynovitis (23%) and large joint involvement (65%). All patients were seronegative for RF and anti‐CCP. Most patients responded well to non‐steroidal anti‐inflammatory drugs or low‐dose prednisone (59%) and remained on immunotherapy (77%). The majority (76%) of patients experienced concomitant irAE in other organ systems. Sixty‐five percent of patients had complete response of their malignancy to immunotherapy. Conclusion: Rheumatic irAE are heterogenous clinical entities, which require further evaluation into classification, patient susceptibility and response. From our study, there was no clear clinical pattern. The present case series supports that rheumatic irAE may be associated with tumour response. However, there is still limited experience in rheumatic irAE management and outcomes.